Islamic banking: products, theory, practice & issues - Kayadibi, Saim (Bilsam Yayıncılık, 2011)
The second conference of the foundations of Islamic finance series: Islamic banking products, theory, practice and issues held at Kuala Lumpur from March 8 to 9, 2011, was as much a great opportunity as for academicians, industrialists, practitioners and students. This foundations began to organize conferences with the support of an Australian Research Council Industry Large Grant for research on Islamic Banking over 2007-2008. The conference is organized by Graduate School of Management (GSM) of University Putra Malaysia with two aims: “a- to create a forum for serious public discussion relating the new emerging industry and academic discipline, Islamic Finance, and b- to produce peer-reviewed quality publications of books and journal articles of high quality on industry issues.” The University Putra Malaysia (UPM) had in the first instance contemplated regional meetings in Melbourne and Dubai then it was felt that the time and world agenda now prevailing in this field made the summoning of a continental conference the more appropriate course organizing it jointly with International Shari‘ah Research Academy for Islamic Finance (ISRA), International Centre for Islamic Finance (INCEIF), Association of Islamic Banking Institutions Malaysia (AIBIM).